MANAGEMENT OF DRINKING WATER SUPPLY SYSTEM (UMBULAN) IN OPEN GOVERNMENT CONTEXT (Universitas 17 Agustus 1945 Surabaya, 2021)
The Drinking Water Supply System (Umbulan) project was planned for 43 years but only realized in 2016. The failure of the Umbulan SPAM project cooperation was caused by the project that was not financially feasible and the tariff applied was too high. In 2012 the Vice President of the Republic of Indonesia Boediono initiated the concept of Open Government to be applied to private companies or state-owned enterprises. The purpose of this study was to determine the application of the concept of Open Government from various relevant stakeholders, namely the Central Government, Provincial Government, District / City Government, related Ministries, PDAB, PDAM, PT PII, PT SMI, and the Community. This study used a qualitative research methodology, while the data collection techniques were carried out by in-depth interviews, FGDs, and empirical observational studies. The results show that most of the relevant stakeholders have implemented the principles of Open Government based on Open Government Indonesia (OGI), OECD, and the Ministry of Transportation. Although some data is not openly provided because it involves secret state documents that cannot be publicly published. The principle of Open Government accelerates coordination among stakeholders related to the Drinking Water Supply System (Umbulan) project.